Metabolic Properties of Some L Forms Derived From Gram-Positive and Gram-Negative Bacteria - Weibull, Claes (1965)
Weibull Claes (Central Bacteriological Laboratory of Stockholm City, Stockholm, Sweden), and Hans Gyllang. Metabolic properties of some L forms derived from gram-positive and gram-negative bacteria. J. Bacteriol. 89:1443–1447. 1965.—L forms of two gram-positive bacteria, a staphylococcus and a diphtheroid, were found to be devoid of catalase and cytochromes, whereas the normal bacteria from which these L forms were derived contained large amounts of these enzymes. On the other hand, L forms of a gram-negative bacterium, Proteus mirabilis, contained the same cytochromes as normal Proteus bacteria. (Previous investigations showed that normal cells and L forms of P. mirabilis contain approximately the same amounts of catalase.) The respiratory quotients (Q(O(2))) of all L forms studied were much lower than those of the corresponding normal bacteria. The conversion of the normal organisms into L forms did not markedly affect their growth rate, measured as the time required for doubling the bacterial mass during the exponential-growth phase.